Qualitative Comparison of Modern Information Technologies Used for System-Information-Analytical Research - Osypenko, V. (Індуктивне моделювання складних систем, 2013)
This paper presents a qualitative comparison of modern methods and information technologies that are used or can potentially be used in innovative system-information-analytical research (SIAR). The sub-criteria system for assessment the quality of major characteristics of such technologies presented from the standpoint of the accepted classification. For comparative analysis a new inductive technology SIAR as intelligent information technology of system analysis of complex systems have been included. У статті подано якісне порівняння сучасних методів та інформаційних технологій, які використовуються або потенційно можуть бути використані в системних інформаційно-аналітичних дослідженнях (СІАД) складних систем. З точки зору прийнятої класифікації представлена система субкритеріїв для оцінки якості основних характеристик таких технологій. Для порівняльного аналізу в якості інтелектуальної інформаційної технології системного аналізу складних систем включена індуктивна технологія СІАД. В статье представлены результаты качественного сравнения современных методов и информационных технологий, которые используются или могут быть использованы в системных информационно-аналитических исследованиях (СИАД) сложных систем. С точки зрения принятой классификации представлена система субкритериев для оценки качества основных характеристик таких технологий. Для сравнительного анализа в качестве интеллектуальной информационной технологии системного анализа сложных систем включена индуктивная технология СИАД.